Downtown Fresno Nuclear Freeze March to and Vigil in Courthouse Breezeway - Watkins, Howard::::::::: (1982)
In courthouse breezeway Reverend Betty Pingel at microphone; Sign: Let There Be Peace on Earth, Let it Begin With Me